Visible Light Photodegradation of Methyl Orange Using α-Fe2O3 Nanoparticles Synthesized via Solvothermal Method in Presence of PVP - َaliakbar Dehno Khalaji; Elham Sadat Zeinoddin; Ali Ghorbani Khorshidi; Ahmad Ghaffari (Nanochemistry Research)
In this study, hematite (α-Fe2O3) nanoparticles were synthesized via solvothermal route and their photocatalytic activity for the degradation of methyl orange (MO) under visible light was studied. The iron precursors solution were prepared by dissolving Fe(NO3)3∙9H2O or Fe2(SO4)3 in an acetic acid glacial/ethanol (9:1 v/v) mixture followed by the addition of polyvinylpyrrolidone (PVP) and urea. The as-prepared α-Fe2O3 nanoparticles were characterized by X-ray diffraction (XRD), vibrating sample magnetometer (VSM), Brunauer-Emmett-Teller (BET), and transmission electron microscope (TEM) techniques. The characterization results confirmed that the α‑Fe2O3 nanoparticles were successfully prepared which had ferromagnetic behavior and micropores with quasi-spherical shapes. The effect of initial pH solution, contact time, and photocatalyst dosage on the photocatalytic degradation of MO was investigated. The photocatalytic results showed the degradation efficiency of 84.3% and 96.8% for MO, after 120 min of visible light irradiation. The photocatalytic examinations illustrated that the degradation of MO follows Langmuir kinetic model with the rate constant (k) of 0.01374 and 0.02689 min-1, respectively.